Mathematical modelling of bioethanol production from algal starch hydrolysate by Saccharomyces cerevisiae - Singh, S.; Chakravarty, I.; Kundu, S. (Cellular and Molecular Biology, 2017)
Bioethanol is an excellent alternative for petrol and has long-term economic advantages over non-renewable liquid biofuels. Bioethanol can be produced from different biomass materials, and it is categorized into three generations by biomass. First generation bioethanol directly competes with food items while second generation bioethanol requires more land area and fertilizers. Bioethanol produced from algae comes under third generation bioethanol and has many advantages over first and second generation bioethanol. Algae have higher growth rates than plants and require less land area also they do not need additional fertilizers for their growth. Microalgae can fix atmospheric CO2 from the environment and assimilate it into lipid and carbohydrates which can be used as a substrate for biofuel production.  In this work, microalgae Chlorella sp. was cultivated at 28oC and light intensity of 25µmol m-2 s-1 and used as a source of starch for bioethanol production. Chlorella starch was hydrolyzed into fermentable sugars by amylases produced from Aspergillus niger NCIM 616 for bioethanol production by yeast Saccharomyces cerevisiae NCIM 3494. Mathematical modelling gave the insight to predict the experimental profiles of bioethanol production from algal biomass.  Microbial growth, reducing sugar consumption, and bioethanol production were described quantitatively by using Logistic, Pirt, and Luedeking-Piret equations respectively.  The equations used in modelling of the fermentation kinetics matched very well with the experimental profiles, thus concluding that ethanol production from algal starch hydrolysate was growth-associated under the evaluated conditions.